Respostas de besouros Scarabaeinae e formigas a distúrbios em savanas tropicais - Carvalho, Raquel Luiza de (2020)
Anthropogenic disturbances are one the main agents of ecosystem degradation, resulting in losses of biodiversity, ecological functions and ecosystem services. These disturbances occur mainly in the tropics; therefore, savannas are among the most threatened environments. The aim of this thesis was to understand the effect of different anthropogenic disturbances on the fauna of the Brazilian and Australian savannas, using dung beetles and/or ants as study organisms. In the first chapter, carried out in the Brazilian savanna, I evaluated the extent to which the conversion of savanna and forest areas into other land uses affects the functional structure of dung beetle assemblages. I found that for almost all functional metrics analyzed, there were significant differences between natural and man-managed habitats. However, these differences were much more marked in the comparisons involving pastures and soy plantations than those involving the eucalyptus plantations. Forest and savanna communities showed very similar responses to conversion to agriculture or pastoral lands. In contrast, my results indicate that conversion to tree plantations has a much greater effect on the forest than on the savanna community. In the second chapter, carried out on Brazilian pastures, I evaluated how the responses to pastoral land management vary between dung beetles and ants, and among functional groups within them. Then I evaluated what environmental and management variables best predict different responses. I found that beetles and ants show contrasting responses to pastoral land management. Ant communities are indicating the importance of vegetation structure, while beetles are indicating the impact of frequency of parasiticide use. In the third chapter, I reported on the first ecological study of dung beetles in the Australian tropical savanna, documenting species composition, food preferences and responses to different fire regimes. My samples were comprised entirely of nine native species of Onthophagus, and dog dung was the most attractive bait. Dung beetle abundance was highest under high fire severity and was negatively correlated with the cover of woody vegetation. Overall, the results of this thesis suggest that land-use changes affect the functional structure of beetle assemblages, and are more pronounced when forests are replaced by man-managed habitats. I also found that beetles and ants provide very different indications of the impact of pastoral land management on biodiversity. Finally, I highlighted that frequent fire promoted dung-beetle abundance through the maintenance of an open habitat structure. In conclusion, the results of this thesis contributed to a better understanding of how the communities of beetles and ants are structured and how they respond to different anthropogenic impacts in tropical savanna regions.